Human Abuse Liability Assessment of Tobacco and Nicotine Products: Approaches for Meeting Current Regulatory Recommendations. Issue 3 (9th September 2021) - Vansickel, Andrea; Baxter, Sarah; Sherwood, Neil; Kong, Michael; Campbell, Leanne
Abstract: Many regulatory bodies now recommend that tobacco product manufacturers provide information regarding new tobacco products' abuse liability to inform regulatory authorization of currently marketed tobacco products or new product applications (including premarket tobacco product applications in the United States). In addition, the US Food and Drug Administration (FDA) recommends including this information as part of modified risk tobacco product applications. Regulators, including FDA, and many public health officials and researchers consider abuse liability assessment a model which predicts the likelihood that the use of the tobacco product would result in addiction and be used repeatedly or even sporadically resulting in undesirable effects. Abuse liability of a new, potentially reduced harm product can also inform its ability to substitute completely for more harmful tobacco products. While many methods exist, no standard tobacco product abuse liability assessment has been established. The purpose of this review is to provide background information and practical recommendations for human abuse liability testing methods to meet tobacco regulatory needs. A combination of nicotine test product pharmacokinetic, subjective effect and/or behavioral response, and physiological response data relative to comparator products with known abuse liability satisfies some regulatory requirements. Implications: This review provides a practical inspection of the current, international regulatory recommendations for abuse liability assessment of tobacco and regulatory review of such information within the United States and also recommends study designs and methods for abuse liability testing of tobacco products based on scientific and regulatory knowledge. Given that tobacco product abuse liability testing is of increasing interest to regulatory bodies globally, especially with the emergence of novel tobacco products, this timely work provides background and functional recommendations for tobacco product abuse liability testing.